Inhibition of Inflammatory Cytokine Expression Prevents High-Fat Diet-Induced Kidney Injury: Role of Lingonberry Supplementation - Madduma Hewage, Susara; Prashar, Suvira; Debnath, Samir C.; O, Karmin; Siow, Yaw L. (Frontiers in Medicine, 2020)
Chronic low-grade inflammation is a major stimulus for progression of chronic kidney disease (CKD) in individuals consuming high-fat diet. Currently, there are limited treatment options for CKD other than controlling the progression rate and its associated complications. Lingonberry (Vaccinium vitis-idaea L.) is rich in anthocyanins with demonstrated anti-inflammatory effect. In the current study, we investigated the potential renal protective effect of lingonberry and its anthocyanin (cyanidin-3-glucoside) in high-fat diet fed obese mice and in human proximal tubular cells. Prolonged consumption of high-fat diets is strongly associated with obesity, abnormal lipid and glucose metabolism. Mice (C57BL/6J) fed a high-fat diet (60% kcal fat) for 12 weeks developed renal injury as indicated by an elevation of blood urea nitrogen (BUN) level as well as an increase in renal kidney injury molecule-1 (KIM-1), neutrophil gelatinase-associated lipocalin (NGAL) and renin expression. Those mice displayed an activation of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) and increased expression of inflammatory cytokines (monocyte chemoattractant-1 (MCP-1), tumor necrosis factor alpha (TNF-alpha, interleukin 6 (IL 6) in the kidneys. Mice fed a high-fat diet also had a significant elevation of inflammatory cytokine levels in the plasma. Dietary supplementation of lingonberry for 12 weeks not only attenuated high-fat diet-induced renal inflammatory response but also reduced kidney injury. Such a treatment improved plasma lipid and glucose profiles, reduced plasma inflammatory cytokine levels but did not affect body weight gain induced by high-fat diet feeding. Lingonberry extract or its active component cyanidin-3-glucoside effectively inhibited palmitic acid-induced NF-κB activation and inflammatory cytokine expression in proximal tubular cells. These results suggest that lingonberry supplementation can reduce inflammatory response and prevent chronic kidney injury. Such a renal protective effect by lingonberry and its active component may be mediated, in part, through NF-κB signaling pathway.